2021
DOI: 10.1155/2021/1308805
|View full text |Cite
|
Sign up to set email alerts
|

A Novel 3D-Printed Device for Precise Percutaneous Placement of Cannulated Compression Screws in Human Femoral Neck Fractures

Abstract: Background. The aim of this study was to investigate the application of computer-aided design and 3D printing technology for percutaneous fixation of femoral neck fractures using cannulated compression screws. Methods. Using computed tomography data, an individualized proximal femur model was created with a 3D printer. The reduction of the femoral neck fracture and the placement of the cannulated compression screws were simulated on a computer. A 3D printing guide plate was designed to match the proximal femur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…An alternative is to use patient-specific drilling guides to translate the planned screw trajectories towards the actual surgery. It has been shown that this permits more accurate and efficient reductions compared with the freehand technique (Schweizer et al, 2016;Merema et al, 2017;IJpma et al, 2021;Long et al, 2021;Nasr et al, 2021).…”
Section: Intra-operative Navigationmentioning
confidence: 99%
See 4 more Smart Citations
“…An alternative is to use patient-specific drilling guides to translate the planned screw trajectories towards the actual surgery. It has been shown that this permits more accurate and efficient reductions compared with the freehand technique (Schweizer et al, 2016;Merema et al, 2017;IJpma et al, 2021;Long et al, 2021;Nasr et al, 2021).…”
Section: Intra-operative Navigationmentioning
confidence: 99%
“…16 studies reported on operation time (Li et al, 2015(Li et al, , 2019Zhang et al, 2015;Liu et al, 2017;Chen et al, 2018Chen et al, , 2019Chen et al, , 2020Hung et al, 2019;Huang et al, 2020;Wang et al, 2020cWang et al, , 2020aBoudissa et al, 2021aBoudissa et al, , 2021bLong et al, 2021;He et al, 2022;Zheng et al, 2022). All studies, except for , found that using computer-assisted planning leads to a significantly shorter operation time compared to conventional planning.…”
Section: Operation Timementioning
confidence: 99%
See 3 more Smart Citations